PROBLEMS IN THE INSTITUTIONAL DEVELOPMENT OF MEDIATION IN THE REPUBLIC OF UZBEKISTAN ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This article elucidates the distinctive features of mediation in alternative dispute resolution and explores promising directions for the development of mediation in our country.